2023
DOI: 10.29333/mathsciteacher/13281
|View full text |Cite
|
Sign up to set email alerts
|

Akan ethnomathematics: Demonstrating its pedagogical action on the teaching and learning of mensuration and geometry

Abstract: The mathematics curriculum implementation depends largely on teachers’ choice of pedagogical skills that would influence meaningful teaching and learning. The suggestive ideal approach this paper presents is to consider exploration and demonstration of Akan (a tribe in Ghana, West Africa) ethnomathematics in the teaching and learning of some selected mensuration and geometrical concepts found in the secondary school curriculum. The study found various Akan ethnomathematical processes supporting the teaching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Research have shown that students view geometry as an essential component of their life when socialcultural concepts are taught to them (Authors, 2023b;Owusu-Darko et al, 2023). There is no disturbance and the students feel comfortable.…”
Section: Introductionmentioning
confidence: 99%
“…Research have shown that students view geometry as an essential component of their life when socialcultural concepts are taught to them (Authors, 2023b;Owusu-Darko et al, 2023). There is no disturbance and the students feel comfortable.…”
Section: Introductionmentioning
confidence: 99%